Analysis of European Experience in solving modern problems in education and science - Tolochko, Svitlana (ScienceRise: Pedagogical Education, 2018)
Normative documents of the European Union in the field of education and science are analyzed, including the EU Framework Program for updated key competencies and establishment of European Qualifications Framework for lifelong education. The need to combine education within the lifelong learning process at all levels, the definition of processes, strategies and plans concerning youth, employment, social integration and research policies in this area is determined. The importance of ensuring the autonomy of universities in the development of curricula and the choice of forms of education, promotion of the development of general competencies is stated. Basic requirements of the Strategy for a reasonable, sustainable and comprehensive growth of Europe 2020 are named, results of research on knowledge, skills and competences of future specialists demanded by Europe in 2030 and further are presented. The key trends of the EU policy in the field of education and culture, the EU “Erasmus +” program and Ukraine’s participation in the EU “Eastern Partnership” initiative, improvement of intercultural understanding, civic participation and ethical awareness, as well as ensuring equitable access to higher education in a united and inclusive society are determined. Worldwide, including the European Higher Education Area, experience of solving educational problems has confirmed the thesis about the importance of integrating competencies of all types, as each of them contributes to a successful life in a knowledge-based society. It is summed up that general knowledge of languages, education, ability to quantitative thinking and awareness in the field of information and communication technologies is the necessary basis for learning, and education for the sake of knowledge includes the whole educational activity. Measures are identified and the goals for ensuring comprehensive and sustainable development, social cohesion and further enhancement of the democratic culture of the European Union countries are set out. In order to progressively develop the European Higher Education Area, it is necessary to intensify interdisciplinary and cross-border cooperation, as well as to develop inclusive and innovative approaches to learning and teaching